DEALING WITH THE INSURANCE BUSINESS IN THE ECONOMIC ACCOUNTS - Harchaoui, Tarek M. (Assurances, 2000)
This article synthetizes and extends the treatment of the insurance business in the system of national accounts, with a focus on the measurement of the production activity. The framework begins with an overall discussion, at the macroeconomic level, on the past and current approaches on the measure of the insurance business production activity in the system of national accounts. But this macroeconomic approach of the insurance business turns out to be limited in many important respects. In extending the framework, I adopt a more disaggregated approach, making a strong case on the need to understand the behaviour and to measure the activity of the insurance business at the level of the line of business. This approach, overlooked by the existing economic literature, provides many insights in terms of the delineation of insurers' lines of business, the measurement of their activity and their interaction within an integrated input-output framework. As a by product, the article also discusses issues related to the regional breakdown of insurers' activities and the unduplicated measure of the insurance firm's output.